Towards diversity : tracing changing constructions of masculinities in some twentieth century film and fiction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Ruzich, Joan (Massey University, 2001)
The theory that masculinities are plural (more than one possible version), socially constructed, and historically produced is supported in this analysis of masculinity in selected American, English, Australian and New Zealand texts of film and fiction across the twentieth century. Post-structural thinking and the psychoanalytic theories of Freud and Lacan, applied to close readings of the selected texts, show that the moment of sexual division must be understood as a product of intense cultural mediation – an event experienced at the suggestion of the society in which men find themselves. The liberal humanist notion of a fixed and coherent self which traditionally was a male self is shown to be increasingly (as the century progresses) displaced by plurality: masculinity is represented diversely, and also increasingly as changing and relational.
Keywords: Mansfield, Katherine, 1888-1923 -- Criticism and interpretation; Prichard, Katharine Susannah, 1883-1969. Working bullocks; Mulgan, John, 1911-1945. Man alone; Best years of our lives (Motion picture); Rebel without a cause (Motion picture); Full monty (Motion picture); Masculinity in literature; Masculinity in motion pictures